Introduction (to "Read this first: growth and development of creative SMEs") - Thomassen, A; Hagoort, G; Van Thiel, M; Arets, D; Oostinjen, A (Research Group Art and Economics, Faculty of Art and Economics at the Utrecht School of the Arts., 2007)
Marian Jacobse is a Utrecht-based sculptor. She is also the director of Sophies Kunstprojecten, which manages more than 15 studio complexes and produces community-oriented arts projects in the city. Its operations are determined by the dilemmas affecting art and commercialism, or more specifically, the creation of art and earning money. The various studios support not only the practice of art by independent artists, but also works produced by creative professionals: people who manage and stage cultural shows in an enterprising manner, based on creative concepts. Jacobse did her arts training in Utrecht and developed her entrepreneurship by acquiring experience, attending courses and, in particular, developing networks. She aspires to keeping the artistic flame burning, while avoiding financial disaster.